REHABILITATION OF CHILDREN WITH SENSORY INTEGRATION DISORDERS AND THE IMPACT OF THERAPEUTIC GAMES - Viktoriia I. Horoshko; Valeriy O. Zhamardiy; Yevheniia O. Skrinnik; Anatolii V. Yemets; Anna V. Fastivets (Клінічна та профілактична медицина, 2025)
Introduction. The use of therapeutic games, modern technologies and an interdisciplinary approach constitutes a promising direction that has the potential to enhance the efficacy of therapy and facilitate the successful integration of children with sensory integration disorders (SID) into the social environment.